TUFT1 Promotes Triple Negative Breast Cancer Metastasis, Stemness, and Chemoresistance by Up-Regulating the Rac1/β-Catenin Pathway - Liu, Weiguang; Chen, Guanglei; Sun, Lisha; Zhang, Yue; Han, Jianjun; Dai, Yuna; He, Jianchao; Shi, Sufang; Chen, Bo (Frontiers in Oncology, 2019)
Objectives: Triple negative breast cancer (TNBC) is a subtype of breast cancer with stronger invasion and metastasis, but its specific mechanism of action is still unclear. Tuft1 plays an important regulatory role in the survival of breast cancer cells; however, its role in regulating TNBC metastatic potential has not been well characterized. Our aim was therefore to systematically study the mechanism of TUFT1 in the metastasis, stemness and chemoresistance of TNBC and provide new predictors and targets for BC treatment. Methods: We used western blotting and IHC to measure TUFT1and Rac1-GTP expression levels in both human BC samples and cell lines. A combination of shRNA, migration/invasion assays, sphere formation assay, apoptosis assays, nude mouse xenograft tumor model and GTP activity assays was used for further mechanistic studies. Results: We demonstrated that silencing TUFT1 in TNBC cells significantly inhibited cell metastasis and stemness in vitro. A nude mouse xenograft tumor model revealed that TUFT1 knockdown greatly decreased spontaneous lung metastasis of TNBC tumors. Mechanism studies showed that TUFT1 promoted tumor cell metastasis and stemness by up-regulating the Rac1/β-catenin pathway. Moreover, mechanistic studies indicated that the lack of TUFT1 expression in TNBC cells conferred more sensitive to chemotherapy and increased cell apoptosis via down-regulating the Rac1/β-catenin signaling pathway. Further, TUFT1 expression positively correlated with Rac1-GTP in TNBC samples, and co-expression of TUFT1 and Rac1-GTP predicted poor prognosis in TNBC patients who treated with chemotherapy. Conclusion: Our findings suggest that TUFT1/Rac1/β-catenin pathway may provide a potential target for more effective treatment of TNBC.